The influence of advertising strategies on corporate performance: A study in the beauty industry - Jie, Fang Wen; Ramachandaran, Sharmila; Sagadavan, Revathi; Doraisingam, Puspanathan (International Journal of Management and Sustainability, 2025)
The purpose of the study is to examine the relationship between advertising investments and enterprise performance within the beauty sector. Through empirical analysis, the study investigates key elements such as budget allocation, channel effectiveness, frequency of advertising campaigns, and creativity in content, culminating in the development and validation of a theoretical model. The findings reveal that budget allocation, advertising channels, and campaign frequency exert a strong influence on corporate performance. However, the creativity and content quality of advertisements are found to have a comparatively weaker impact. Additionally, an inverse relationship is identified between excessive advertising investments and enterprise performance, highlighting a threshold effect. The study emphasizes the importance of strategic balance in advertising investments and suggests that more is not always better in enhancing business outcomes. These insights can guide marketing managers in optimizing advertising strategies, safeguarding resource efficiency, and improving performance outcomes in the beauty sector.